Higher Carotid Intima-Media Thickness in Subclinical Hypothyroidism Associated with the Metabolic Syndrome - França, Mariana Martins [UNESP]; Nogueira, Célia Regina [UNESP]; Hueb, João Carlos [UNESP]; Mendes, Adriana Lúcia [UNESP]; Padovani, Carlos Roberto [UNESP]; Mazeto, Gláucia Maria Ferreira Da Silva [UNESP] (SAGE Publications, 2016)
Background: The subclinical hypothyroidism (SH) and the metabolic syndrome (MS) have been associated with increased risk of atherosclerosis and cardiovascular disease (CVD). The measurement of carotid intima-media thickness (IMT) is capable of detecting early signs of atherosclerotic disease. The goal of the study was to compare the carotid IMT of patients with SH with and without the MS. Methods: Twenty-nine SH patients were subdivided into two groups: one with MS (SH + MS) and one without MS (SH - MS). The study also assessed a group of euthyroid patients (n = 31), also subdivided into two groups: one with MS (EU + MS) and one without MS (EU - MS). The clinical and laboratory data and the mean and maximum carotid IMT of the groups were compared. Results: Maximum (P = 0.012) and mean (P = 0.025) IMT were higher in the SH + MS group than in the SH-MS group. Maximum IMT was higher in the SH + MS group than in the EU + MS group (P = 0.048). Maximum IMT was positively correlated with fasting glucose (FG; R = 0.621; P < 0.01) and body mass index (R = 0.258; P = 0.041) and negatively correlated with low-density lipoprotein cholesterol (LDL-C) (R = -0.297; P = 0.017). Mean IMT was positively correlated with FG (R = 0.580; P < 0.01), systolic blood pressure (R = 0.292; P = 0.02), and triglycerides (R = 0.250; P = 0.048) and negatively correlated with LDL-C (R = -0.288; P = 0.022). Conclusions: SH + MS patients have higher IMT than SH - MS or EU + MS patients, suggesting that SH may be one more CVD risk factor in patients with the MS.
Keywords: atherosclerosis; cardiovascular disease; carotid intima-media thickness; hypothyroidism; metabolic syndrome; subclinical hypothyroidism